Mutual Defense Scheme for Secure Data Aggregation in Wireless Sensor Networks. (25th June 2014) - Rong-hua, Hu; Xiao-mei, Dong; Da-ling, Wang
Abstract : As a resource-saving technique, data aggregation has been intensively studied in wireless sensor networks (WSNs). However, existing methods of secure data aggregation in WSNs either (1) cause high communication overhead or (2) cannot defend against compromised member nodes and aggregator nodes at the same time. In this paper, we propose a mutual defense scheme for secure data aggregation, which includes two components, that is, secure sort-group-filter data aggregation algorithm (SSGF) and lightweight TDMA-based monitoring mechanism. The SSGF is to defend against injecting false readings by compromised member nodes, and the monitoring mechanism is to defend against altering the aggregation results by aggregator nodes. In addition, a secure data packet transmission scheme is also presented. Considering that the readings sensed by neighbor nodes exhibit temporal and spatial correlation, a constraint parameter, called maximum tolerant difference (MTD), is introduced and the quantitative criteria for abnormal readings evaluation are given. Both the theoretical analysis and comparative experiments show the feasibility and efficiency of the proposed method.